Immunohistochemical Expression of MMP2, VEGF and D2-40 as Biological Markers of Local Invasion Potential, Angiogenesis and Lymphangiogenesis in Oral Squamous Cell Carcinoma and Verrucous Carcinoma - Roqaia G. Baqer; Bashar H. Abdullah (College of Dentistry/ University of Baghdad, 2016)
Background: Verrucous carcinoma (VSCC) is considered as a rare well differentiated carcinoma variant of SCC with no metastatic potential. The aim of this study is to evaluate the Immunohistochemical expression MMP-2, VEGF and D2-40 expression in OSCC and VSCC. Materials and methods: Thirty formalin fixed paraffin embedded tissue blocks of OSCC and another twelve VSCC were collected and Four micrometer thick sections were cut from each block and mounted on positively charged slides and stained immunohistochemically with monoclonal antibodies to MMP-2, VEGF and D2-40. Results: there is no statistical difference between SCC and VSCC regarding the immunoexpression of MMP-2 and VEGF. While the lymphatic vessels density were higher in SCC than VSCC Conclusions: OSCC and VSCC bear similar local invasion and angiogenesis potentials when quantified with MMP-2 and VEGF immunostaining respectively whereas OSCC have higher lymphatic vessels density than their VSCC as evaluated with D2-40 immunoexpression